Comparação entre Técnicas de Espectrometria Atômica para Determinação de Mercúrio em Sedimento Marinho - Provete, Carolina Scocco (2021)
The determination of mercury Hg in marine sediment is an analytical challenge due to its toxicity even at low concentrations, which is the level generally found in nature, thus requiring the use of analytical techniques that have high sensitivity and low limits of quantification. Therefore, the use of ICP-MS (Inductively Coupled Plasma Mass Spectrometry), CV-ICP OES (Inductively Coupled Plasma Optical Emission Spectrometry with Cold Vapor Generation) and DMA-80 (Direct Mercury Analyser) were evaluated for the determination of mercury in marine sediment samples. After verifications and optimizations in the ICP-MS, CV-ICP OES and DMA-80 methodologies, were determined the limits of quantification (LQ) of 1.9, 165 and 0.35 μg . kg-¹, respectively, as well as a statistical agreement between the determined and the certified values in the NIST 2702 Marine Sediment certified reference material. To evaluate possible interferences due to the high salinity of marine sediment samples, was performed a comparison of determinations between samples collect in Espírito Santo Bay that underwent the washing process (L) with those that were not washed (SL). There was a statistical difference in Hg concentration between L and SL samples determined by both ICP-MS and DMA-80, maintaining the trend of higher values in SL samples. In this way, considering that mass loss may have occurred during the washing procedure despite the long sedimentation time, that the washing step decreases the analytical frequency and that an adequate relative standard deviation (RSD) value was obtained for the samples without washing, it was chosen as the procedure not to wash the samples. The results obtained by the CV-ICP OES technique, both in samples that went through the washing process and in those did not, due to the high LQ value obtained (165 μg . kg-¹). Although the methodology that used de CV-ICP OES technique was not sensitive for the determination of Hg in the samples it could be used to indicate the classification according to the criteria established by CONAMA Resolution (National Environmental Council). No. 454 of 2012 - sediment quality in relation to Hg, which establishes as 300 μg . kg-¹ the level above which there is a probability of adverse effect on the biota. The methodologies that used ICP-MS and DMA-80, in addition to being adequate to verify the CONAMA criteria, were also suitable for monitoring low levels of Hg in marine sediment samples and comparison with international sediment quality guides.